Characterisation of the hydantoin-hydrolysing activity of pseudomonas putida strain RUKM3s and development of biocatalyst for amino acid production - Bulawayo, Bernard T (Department of Chemical Engineering, 2023)
This study tested the hypothesis that the hydantoin-hydrolysing enzymes of a novel Pseudomonas putida, RUKM3s, with high-levels of activity of a non-stereoselective hydantoinase, and an L-selective N-carbamyl amino acid amidohydrolase (NCAAH), could be optimally extracted, partially purified for characterisation, stabilised by immobilisation, and applied as a biocatalyst for production of amino acids from 5-mono-substituted hydantoin substrates. Experiments were devised to optimise conditions for the production of RUKM3s biomass with high levels of hydantoin hydrolysing activity, and to evaluate techniques of protein extraction, enzyme isolation, purification and characterisation. The NCAAH ofRUKM3s is a dimer of approximately 60 k:Da, .with two subunits of approximately 30 k:Da each. The hydantoinase · is approximately 210 kDa. Methods of enzyme immobilisation were investigated and operational parameters of the immobilised biocatalysts were evaluated. Stabilisation of biocatalysts by immobilisation revealed that among five methods of immobilisation used, covalent coupling to Eupergit® C provided the most suitable biocatalyst formulation of the RUKM3s enzymes. A model of the hydantoinase reaction based on the stabilised biocatalyst was developed and tested by empirical studies in a bioreactor system. In the system, the high hydantoinase activity from RUK.M3s was coupled with the high NCAAH activity of a mutant Agrobacterium tumefaciens strain, RUOR-PNI, to enhance the overall product yield. It was . demonstrated that the combined bioreactor system could achieve close to 100 % conversion yields of amino acid, operating in a continuous substrate-feed mode.